A Genomic Study in Octoploide Triticale (8x) and their Genitors (Wheat and Rye) by C-banding, N-Banding and In Situ Hybridization: The Translocation Identification 2BL/7RS - Dounia Hammouda; Nadra Khalfallah; Houda Badri Mohammed (Recent Research Advances in Biology Vol. 10, 2021)
Objective: The main objective of this study is to analyze the heterochromatin (DNA sequences non-coding rich in CG base) genomes of a primary triticale, and their progenitors, wheat and rye on the one hand, and on the other to Localizes the nuclear organizer regions (NOR) and ribosomal genes (5S and 45S). Methodology and Results: The Analysis of C bands of genomes the hybrids are in a comparison with their genitors displayed a different marking. In the genomes A, hybrid (Mahon-demiasxRC9) is less heterochromatic than the genitor D (Mahon-demias). The genomes B and D of the hybrid (Mahon-demias xRC9) show a richness in heterochromatin relative to their homologous of the D genitor. Nevertheless, in R genome of hybrid (Mahondemias xRC9) is almost similar to its E genitor (RC9), except the 2BL / 7RS chromosome. In the genitors and in the hybrids, the organizing regions (NOR) marked on the chromosomes 1R, 2R, 3R and 6R of rye and on the chromosome 1B of wheat and on the chromosomes 1B, 1R, 2R, 3R, 6R of triticale, showed the same localization compared with that is described by authors. The molecular analysis shows that, 5S locus is co-localized with the 45S locus on the chromosome 5R. The 45S loci are located on the 1R, 3R, 5R and 7R chromosomes. They correspond to the nuclear organizer regions (N.O.R). While in triticale, 5S loci are located on chromosomes 2A, 5B and 7RS / 2BL. The 45S locus is located on chromosomes 1R, 3R and 7RS / 2BL. Contrary to the bibliography, the chromosome 5R shows two loci 5S and 45S co localized on the telomer of the short arm. This result suggests that the variety of rye that served as genitor acquired during its selection of rDNA that it transmits to his descendants in a stable manner. 7RS / 2BL Translocation highlighted by C-banding is confirmed by FISH. Conclusion and Application of Results: The results indicate the existence of intervarietal and interspecific polymorphisms in rye and triticale, as well as the presence of chromosomes B of telocentric form or isochromosomes a heterochromatic and / or euchromatic structure. In a conclusion, we establish a molecular cytogenetic mapping of marker chromosomes and ribosomal genes of our vegetal material (genitors and hybrid).